Inhibiting Bcl-2 via its BH4 domain in DLBCL cancers to provoke pro-apoptotic Ca2+ signaling - Kerkhofs, Martijn (Student Undergraduate Research E-journal!, 2015)
Some DLBCL cancers are sensitized to programmed cell death at the ER by upregulation of the IP3R2. These cancers express Bcl-2 in abundance to prevent pro-apoptotic IP3R2-mediated Ca2+ signaling. BIRD-2 (Bcl-2/IP3R Disruptor-2) is a newly developed peptide that disrupts the complex of Bcl-2 and the IP3R, thereby provoking toxic Ca2+ signaling. However, the exact working mechanism of this peptide has not been characterized. We report a possible role for the mitochondria as downstream effectors of BIRD-2-induced cell death and validated a calcein-AM/CoCl2 staining to assess mPTP opening in response to BIRD-2.